Systematic literature review of convergence: A systems perspective and re-evaluation of the convergence process - Klarin, Anton; Suseno, Y.; Lajom, J.A.L. (2021)
This article examines convergence by providing a systematic literature review using scientometric method. Despite the steady growth of convergence literature, we still have an incomplete understanding of convergence concepts as well as the processes of industry convergence (IC). Our systematic review highlights several key findings. First, our review highlights six clusters of research on convergence. Second, our analysis suggests that the process of convergence does not necessarily progress in the three- to four-step supply-side process as postulated in the literature, i.e., from scientific convergence, technology convergence, market convergence, and finally to IC. Although existing literature suggests that IC occurs as a result of supply-side convergence, we expand on this proposition and put forth market-driven convergence processes. Third, we provide a typology of the convergence concepts to bring clarity and avoid indiscriminate use of the various convergence concepts. Finally, our article offers new debates on the literature of convergence, providing scholars with research directions that extend beyond the standard convergence processes. Our systematic review is relevant to scholars and managers as the study highlights a taxonomy of convergence scholarship, a typology of convergence concepts, and a re-evaluation of the IC process model to drive the research forward.